(3GdbhGYO GdELQGFjI ai bGfhf GdCMcGe GdYScQjI (B: s (3OQGSI ebGQfI Hjf LeghQjI eUQ GdYQHjI hSdWfI YeGf (B/ s - (3NdaGf Hf SYjO Lejd GdSYOi s; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JHjf GdOQGSI JYQja GdbGfhf GdYScQi hJWhQg hGdYdGbI Hjf GdLgGJ GdJi JJhdi JWHjbg hcPdc NUGFU GdbGYOI GdbGfhfjI ddbGfhf hfTCI GdbGfhf GdYScQi MSH GdMVGQGJ GdeNJdaI Ke GLQGAGJ GdJMbjb h GdeMGceI ai GdbGfhf GdYScQi ShGA ai eUQ Ch YeGf HOC ef GdJMbjb ai GdfjGHI GdYScQjI hGdELQGAGJ GdeJHYI MJi SjQ GdeMGceI hELQGAGJgG hCfhGY GdeMGce GdYScQjI eY JhVjM ENJUGU gPg GdeMGce eY GdJCcjO Ydi Ef GdbVGA GdYScQi bVGA LfGFi NGU eY YOe LhGR GdEOYGA GdeHGTQ CeGe GdbVGA GdYScQi ai GdLfGjGJ hGdLfM hYOe LhGR GdEOYGA HGdMbhb GdeOfjI CeGe GdbVGA GdYScQi ai GdLQGFe GdYScQjI HeNJda eSJhjGJgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2010s
(3HHdjhLQGajG(B: (3UaMGJ (B479-505s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3CMcGe GdeMGce GdYScQjI s; (3GdbhGYO GdELQGFjI s; (3GdfjGHI GdYScQjIs; (3GdeOYi GdYGe GdYScQis; (3GdbVGA GdYScQi GdYeGfis; (3GdLQGFe GdYScQjIs; (3GdeMGce GdYScQjIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs